A Novel DNA Methylation Signature as an Independent Prognostic Factor in Muscle-Invasive Bladder Cancer - Xu, Zhijie; Gujar, Hemant; Fu, Guanghou; Ahmadi, Hamed; Bhanvadia, Sumeet; Weisenberger, Daniel J.; Jin, Baiye; Gill, Parkash S.; Gill, Inderbir; Daneshmand, Siamak; Siegmund, Kimberly D.; Liang, Gangning (Frontiers in Oncology, 2021)
Background: Muscle-invasive bladder cancer (MIBC) accounts for approximately 20% of all urothelial bladder carcinomas (UBC) at time of diagnosis, and up to 30% of patients with non-muscle invasive UBC will progress to MIBC over time. Increasing body of evidence has revealed a strong correlation between aberrant DNA methylation and tumorigenesis in MIBC. Results: Using The Cancer Genome Atlas (TCGA) molecular data, we described a DNA methylation-based signature as a prognostic factor for overall survival (OS) in patients with MIBC. By using a least absolute shrinkage and selection operator (LASSO) model, differentially methylated regions were first identified using multiple criteria followed by survival and LASSO analyses to identify DNA methylation probes related to OS and build a classifier to stratify patients with MIBC. The prognostic value of the classifier, referred to as risk score (RS), was validated in held-out testing set from the TCGA MIBC cohort. Finally, receiver operating characteristic (ROC) analysis was used to compare the prognostic accuracy of the models built with RS alone, RS plus clinicopathologic features, and clinicopathologic features alone. A DNA methylation signature was generated using a DNA methylation array from 413 MIBC patients. We found that our seven-probe classifier-based RS, stratifies patients into high- and low-risk groups with higher predictive value for overall survival (OS) in the training (n=276) (AUC at 3 years, 0.73; AUC at 5 years, 0.75) and testing (n=137) (AUC at 3 years, 0.65; AUC at 5 years, 0.65) sets compared to a model composed of only clinicopathologic features. In addition, RS significantly improved the prognostic model when it was combined with clinical information including age, smoking status, Tumor (T) stage and Lymph node metastasis (N) stage. Conclusions: The DNA methylation-based RS can be a useful tool to improve the predictive accuracy of preoperative and/or post-cystectomy models of OS in MIBC patients.